Ancestor approved : intertribal stories for kids - Smith, Cynthia Leitich (Heartdrum, an imprint of HarperCollinsPublishers, 2021)
Edited by award-winning and bestselling author Cynthia Leitich Smith, this collection of intersecting stories by both new and veteran Native writers bursts with hope, joy, resilience, the strength of community, and Native pride.